1996
DOI: 10.1111/j.1440-1754.1996.tb00907.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and aetiology of neurological impairment in extremely low birthweight infants

Abstract: Intellectual impairment was associated with a broad range of perinatal variables. Cerebral palsy was associated with fewer variables, all of which were also associated with intellectual impairment. Neurologic injury was associated with male sex and multiple birth, which are not biological insults themselves, but may be markers of susceptibility to injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…This is consistent with previous findings (Waugh et al, 1996;Lagunju et al, 2006;Hamzat and Fatudimu 2008;Boskabadi et al, 2010;Frank-Briggs and Alikor, 2011). However, this is at variance with the findings of Buljina et al (1999), who reported an insignificant gender difference in children with CP in their study.…”
Section: Demographic Characteristics Of the Participantssupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous findings (Waugh et al, 1996;Lagunju et al, 2006;Hamzat and Fatudimu 2008;Boskabadi et al, 2010;Frank-Briggs and Alikor, 2011). However, this is at variance with the findings of Buljina et al (1999), who reported an insignificant gender difference in children with CP in their study.…”
Section: Demographic Characteristics Of the Participantssupporting
confidence: 93%
“…Various risk factors have been linked to the occurrence and types of CP (Waugh et al, 1996;Hutton and Pharaoh, 2002). Children of teenage mothers or fathers were reported to be at risk of CP, and a significantly higher prevalence of CP was also reported in children whose mothers were 40 years or older, especially if such children were high in parity (Cummins et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Those factors considered to be the most predictive, such as cerebral ultrasound studies [11] or neonatal EEG [12], are a consequence or a marker of a pre-or postnatal aggression rather than a risk factor. Some true risk factors such as male gender, label a particular susceptibility to injury [13]. Other events, such as ductus arteriosus, prolonged ventilation, blood transfusion [9], and bronchopulmonary dysplasia [6], are associated with extreme and complicated prematurity.…”
mentioning
confidence: 99%
“…Ventricular dilatation was associated with CP and even more strongly with intellectual impairment [Waugh et al, 1996]. Murphy et al [1996] recently reported that 16 of 18 preterm children with CP had cystic lesions of brain parenchyma noted on neonatal ultrasound examination.…”
Section: Neonatal Findings In Vlbw Infants and Risk Of Cpmentioning
confidence: 98%